INVESTIGATION OF UNDERWATER FRICTION STIR WELDING ON 5052 ALUMINIUM ALLOY TO OPTIMIZE THE JOINT STRENGTH - PARAMAGURU, DHANIS (2019)
Underwater Friction Stir Welding (UFSW) has been conducted on 5052-aluminum alloy of 6-mm thickness plate at various tool rotational speeds, welding speeds and type of welding tools.